Crime survey for England and Wales, 2011-2012: teaching dataset (Crime Survey for England and Wales, 2013)
The Crime Survey for England Wales 2011-2012: Teaching Dataset is based on the Crime Survey for England Wales 2011-2012 (available from the UK Data Archive under SN 7252) and constitutes real data which are used by the government and are behind many headlines. The teaching dataset contains fewer variables and has been subjected to certain simplifications and additions for the purpose of learning and teaching. The main differences are: the number of variables has been reduced, weighting has been simplified, a reduced codebook is provided, additional continuous variables have been created (using principle components analysis of pre-existing variables) in order to facilitate their use in quantitative methods classes.